Weathering conflict: The effect of resource shocks on livestock raids - Jensen, Nathaniel D.; López-Rivas, Jose D.; Morsink, Karlijn; Rikken, Emma E. (University of Oxford Centre for the Study of African Economies, 2025)
We examine the impact of climate shocks and drought insurance on inter-communal pastoral conflict in Kenya and Ethiopia. Using NASA’s eMODIS satellite data on pasture availability and a 40-season longitudinal household dataset, our findings highlight the dual role of pasture scarcity and pasture abundance in driving conflict, contingent on seasonal timing. Negative shocks leading to pasture scarcity increase conflict in dry seasons, while positive shocks that lead to pasture abundance fuel conflict in subsequent rainy seasons. Leveraging exogenous variation in drought insurance, we find that while insurance reduces conflict on average, this masks important heterogeneity. Ex post indemnity payments mitigate conflict during droughts, but ex ante insurance coverage exacerbates conflict when pasture is abundant in rainy seasons. These findings highlight the dual relationship between resource availability and conflict, and the importance of considering the impact of policy interventions in this light.